Exploring the Role of Cultural Intelligence in Driving Innovation: Evidence from Systematic Review and Industry Practices - Johny Budiman; Wisnu Yuwono; Edy Yulianto Putra; Suyono Saputra (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Although research on cultural intelligence remains limited, interest in the topic has grown significantly in recent years. Since cultural diversity and cultural understanding play important roles in innovation, cultural intelligence is increasingly recognized as a critical factor for organizational competitiveness. A key challenge related to cultural intelligence (CQ) lies in the gap between increasing workplace cultural diversity and organizations’ limited capability to manage it effectively. This lack of CQ hinders collaboration, knowledge sharing, and innovation performance, preventing organizations from fully leveraging diversity for competitive advantage.Purpose: This study aims to analyze the theoretical and practical influence of cultural intelligence on innovation, particularly within the service industry.Design/Methodology/Approach: A qualitative approach was employed through a systematic review of 42 Scopus-indexed journal articles, involving the identification, evaluation, and interpretation of relevant studies. The findings from the review were further enriched with quantitative insights drawn from exploratory interviews with eight industry practitioners, analyzed using a simple scoring approach.Findings/Results: The results reveal that only 30.6% of the CQ practices identified in the literature were found to be implemented by the surveyed companies. Moreover, the study identifies emerging variables in cultural intelligence development, including the creation of a harmonious and flexible work environment between senior and junior employees, competitive advantage, alignment of organizational culture with business strategy, and customer demand generation.Conclusions: The findings suggest that companies should better leverage their available resources to enhance cultural intelligence, thereby fostering greater innovation capacity. Key actors, including top management, HR professionals, team leaders, and employees, play essential roles in developing and implementing cultural intelligence. Each contributes strategically to embedding CQ through leadership, talent management, training, and collaborative practices that enhance innovation and competitiveness.Originality/Value (Sate of the Art): This research contributes to the literature by integrating systematic review with industrial practice analysis, highlighting underexplored cultural intelligence variables and offering state-of-the-art insights into how cultural intelligence can be leveraged to strengthen innovation in the service sector. Keywords:  cultural intelligence, innovation, systematic review, service industry, organizational culture